1993
DOI: 10.1172/jci116812
|View full text |Cite
|
Sign up to set email alerts
|

Antigen mimicry in autoimmune disease sharing of amino acid residues critical for pathogenic T cell activation.

Abstract: A nonamer peptide from murine nicotinic acetylcholine receptor a chain (ACR8), which shared four amino acid residues with a nonamer peptide of murine ovarian zona pellucida glycoprotein ZP3, induced murine autoimmune oophoritis and IgG autoantibody to the zona pellucida. Crossreaction between the ACR5 and ZP3 peptides was established by the response of a ZP3 peptide-specific, oophoritogenic T cell clone to both peptides in association with 1A(d'#). By substituting the ZP3 peptides with a single alanine, four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 31 publications
1
28
0
1
Order By: Relevance
“…In summary, although there is considerable evidence that autoimmune disease can be elicited by exogenous Ag through molecular mimicry at the level of T or B cell response (43,44), research based on the AOD and other spontaneous autoimmune models emphasize a more critical role for endogenous Ag in the prevention, induction, and maintenance of pathogenic autoimmune responses. In a recent study, we documented the requirement of endogenous Ag for the maintenance of physiological tolerance to ovarian self Ag (45).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, although there is considerable evidence that autoimmune disease can be elicited by exogenous Ag through molecular mimicry at the level of T or B cell response (43,44), research based on the AOD and other spontaneous autoimmune models emphasize a more critical role for endogenous Ag in the prevention, induction, and maintenance of pathogenic autoimmune responses. In a recent study, we documented the requirement of endogenous Ag for the maintenance of physiological tolerance to ovarian self Ag (45).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed in a panel of 600 anti-viral mAb that as many as 3.5% cross-react with mammalian proteins," In experiments using mice constitutively expressing the hcl-2 gene that inhibits apoptosis and hence, clonal deletion, antibodies to dsDNA were generated after immunization with the bacterial hapten pneumococcal cell wall. '-Many experimental or clinical examples of auto-antibodies could have been cited here to support the existence of autoantibodies in the peripheral B cell repertoire but this paper'-is particularly pertinent to the topic of mimicry since the elicitor of the anti-dsDNA antibodies was a bacterial hapten.…”
Section: Cross-reactive Auto-antihodiesmentioning
confidence: 99%
“…This phenomenon may initiate and/or perpetuate autoimmune disease (8). Consistent with this theory, a number of animal studies have demonstrated that Ag mimicry can induce a T cell response in addition to autoimmune disease in the form of murine autoimmune oophoritis (9), and limited sequence homology can evoke a multiple sclerosis (MS)-like disease (10).…”
mentioning
confidence: 87%